What kids should know about Filipino food - Sta. Maria, Felice Prudente (Adarna House, 2016)
Food is not just what we eat. It is what make us unique as a people. Some have called it our "edible identity". In our food, we find traces of our past and present history. In the way we eat, we show how we celebrate our family and our community. Bacause it is so commonplace in our lives, we often forget that food is part of our cultural heritage. Find out more about Filipino food and what makes it Filipino.